Tragedi Tanah: Menyelusuri Pelanggaran Hukum dalam Sengketa Hak Milik - Gunawang Gunawang; Sitti Khadijah Nur Fajri (Jurnal Litigasi Amsir, 2023)
A land title certificate is valid proof of the outcome of the land registration process. According to Article 19 paragraph (2) of the UUPA, registration involves a series of activities that culminate in the granting of a certificate as proof of legal ownership. The certificate, the form of which is determined by the Minister, is a copy of the land book or picture of the situation stitched together. Land with a certificate has been registered in accordance with applicable laws and regulations, indicating legal ownership.